Study on wear mechanism of solid carbide cutting tool in milling CFRP - Muhamad Khairussaleh, Nor Khairusshima; Che Haron, Che Hassan; A. Ghani, Jaharah (Cambridge University Press, 2016)
Carbon fiber reinforced plastic (CFRP) is an expensive composite which has become valuable material as the demand for this composite increased in the industries. It is suitable to be used in automotive, aerospace, and aircraft because of its properties which is stronger than steel and also stiffer than titanium while retaining its lighter weight. However machining of CFRP is a mess to machinist due to its nature which is abrasive. The paper presents the wear mechanism on solid carbide cutting tool during milling CFRP. The wear mechanism is observed under dry and chilled air machining. The machining parameters tested were at cutting speed of 200 m/min with constant feed rate and depth of cut. For both dry and chilled air machining, it is observed that carbide cutting tool experienced abrasive wear which has been influenced by abrasive powdering chips and fibers during milling CFRP. Under microscope and scanning electron microscope, the abrasive wear is represented by shiny and polish area on the cutting tool respectively. This abrasive wear is observed higher under dry machining compared to the chilled air machining which was due to the heat generated during machining. Thus, chilled air has a potential of improving machinability of CFRP by using solid carbide cutting tool.